PERAN STRATEGIS PENGADILAN AGAMA DALAM PENYELESAIAN SENGKETA EKONOMI SYARI`AH - Andi Fariana (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2015)
One of the factors that give the highest contribution in the growth of national economy is the growth of sharia economy. The fast growth of sharia economy makes a dispute settlement is one of the thing that has to be noted. Religious courts as a litigation institution that have the absolute authority based on Undang-Undang Peradilan Agama and enforced with the Keputusan Mahkamah Konstitusi No. 93 Tahun 2012 have the advantage and obstacles on its own, from the perspective of the history of the existence of religious court or from the perspective of sharia economy dispute settlement authority. The research of history of religious court in Indonesia and research on the advantages and obstacles of religious courts in carrying out the absolute authority has bring forth a conclusion that the appointment of religious courts as the institute that have an absolute authority in dispute settlement of sharia economy is very precise but needs to be enforcement from the institutional and human resource aspect. It also needs to be supported with the release of religious court law proceedings and the consideration to appoint an ad hoc judge to develop a faster justice system.Copyright (c) 2016 by Al-Ihkam. All right reservedDOI: 10.19105/al-ihkam.v10i2.720